British short fiction in the early nineteenth century : the rise of the tale - Killick, Tim (Ashgate, 2008)
Contextualizing British short fiction within the broader context of Romantic-era print culture, Tim Killick argues that authors such as Washington Irving, Mary Russell Mitford, and James Hogg championed the use of short fiction during a period predominantly associated with novel-writing and poetry. His book makes a convincing case for the evolution of short fiction into a self-conscious and modern genre, with its own techniques and imperatives, separate from those of the novel.